Orientation of functional zoning for sustainable use of environment and natural resources in Tien Yen Bay - Tuấn, Hoàng Văn; Quy, Trần Đăng; Vượng, Nguyễn Văn; Nhuận, Mai Trọng (Vietnam Journal of Earth Sciences, 2013)
Tien Yen bay which is located in the coastal province of Quang Ninh plays an important role in socio-economic development of the region and national territorial sovereignty protection. In addition, Tien Yen bay is rich in natural resources, especially coastal wetlands and biological resources. However, the imbalance trend of the geochemical cycle threatening the sustainability of the bay has been observed as the results of exploitation activities and irrational use of coastal wetlands (e.g., destruction of mangrove ecosystems, overfishing, and high aquaculture density in intertidal wetlands). Although socio-economic development planning has been proposed and implemented, the functional values of natural resources and environment have not been taken into account. The results of recent status and characteristics of resources and environment of Tien Yen bay indicate that the study area can be divided into seven functional areas of environment for various development purposes which are suitable with current status of natural resources, geochemical and socio-economic characteristics: Area I - Dong Rui nature and wetland conservation; Area II - development of Mui Chua port; Area III - conservation and development of mangrove associated with eco-fishing in Tien Yen - Hai Ha; Area IV - wetland conservation associated with aquaculture in tidal flat and eco-fishing in the remaining area of Tien Yen - Hai Ha; Area V - nature conservation associated with aquaculture cages, fishing restrictions in Nui Cuong - Hon Mieu; Area VI - Hai Ha industrial and seaport development; and Area VII - sea and island economic development associated with national security and defence in Cai Bau - Vinh Thuc.